New insights on stratigraphy and sedimentology of the Oncala Group (eastern Cameros Basin): implications for the paleogeographic reconstruction of Iberia at Berriasian times - Quijada, I.E.; Suarez-Gonzalez, P.; Benito, M.I.; Mas, R. (Journal of Iberian Geology, 2013)
The Berriasian Oncala Group of the eastern Cameros Basin is a key element for the paleogeographic reconstruction of NE Iberia during this period of time, due to its intermediate position between the Basque-Cantabrian, southern Iberian, and Pyrenean Basins. The Oncala Group, which comprises up to 2500 m of sediments, consists of siliciclastic deposits in western areas of the basin, which pass gradually eastwards and upwards to carbonate-evaporitic deposits. The siliciclastic deposits consist of an alternation of laterally extensive laminae of siliciclastic mudstone and sandstone, and meander loop bodies. The carbonate deposits are made up of an alternation of laminae of carbonate mudstone and pseudomorphs after gypsum, interbedded with shales and carbonate breccias. These deposits had been traditionally interpreted as formed in fluvial and alluvial systems, and laterally related lakes, but recent and new sedimentological data discussed in this paper suggest that they were deposited in broad, siliciclastic tidal flats, laterally associated with a fluvial system to the west, and with shallow, coastal, carbonate-sulphate water bodies to the east. The development of these coastal environments in the Oncala Group indicates that a wide, shallow, coastal embayment was developed in the eastern Cameros Basin during the Berriasian. This new paleoenvironmental interpretation makes necessary a revision of the paleogeographic reconstruction of this area of Iberia during the Berriasian because it implies that the connection of the Cameros Basin with marine areas was much more important than previously considered. The presence of very similar facies associations in the Basque-Cantabrian Basin, which include siliciclastic tidal and lagoonal deposits in the western areas, and evaporites and carbonates of restricted marine environments in the eastern areas, the similar sulphur isotope compositions of the sulphates of the Basque-Cantabrian and Cameros Basins, and the similar vertical evolution of the Berriasian deposits of both basins, suggest that the Cameros Basin was connected with marine and transitional areas of the Basque-Cantabrian Basin during Berriasian times. Nevertheless, a connection with the southern Iberian Basins, which also contain siliciclastic and carbonate tidal deposits, cannot be excluded.